Writing, Affordances, and Governable Subjects - George, Mark K. (Journal for Religion, Film and Media, 2021)
The book of Deuteronomy in the Hebrew Bible makes a number of references to writing and to the importance of Israel carefully observing the commands, statutes, and ordinances written in the book. Readers can then conform themselves and their behaviors according to the subjectivity of Israel the book sets forth. The process of conforming oneself to what is written in a book makes use of particular affordances of writing, a technology that was becoming more widespread at the time Deuteronomy was being written. The materiality of the book and the social uses to which writing and books could be put are being realized in Deuteronomy in order to create people as particular subjects called “Israel.”